The abundance and characteristics of atmospheric microplastic deposition in the northwestern South China Sea in the fall. (15th May 2021) - Ding, Yongcheng; Zou, Xinqing; Wang, Chenglong; Feng, Ziyue; Wang, Ying; Fan, Qinya; Chen, Hongyu
Abstract: Atmospheric microplastics have been widely reported and detected in remote mountain areas and oceans, indicating that they can be transported over long distances through the atmosphere. Regional transport and deposition processes of atmospheric microplastics have a significant impact on the source and sink patterns, as well as the flux mechanisms of microplastics in terrestrial and marine environments. However, few studies have been conducted on the deposition of atmospheric microplastics. Thus, in this study, we collected atmospheric microplastic samples from the northwestern South China Sea and estimated that in the fall the dry deposition of atmospheric microplastics into the ocean was 1.4 × 10 3  t, which had a greater contribution than riverine inputs of microplastics in this region, suggesting that atmospheric microplastics are non-negligible sources of marine plastic litter with high environmental risk. Additionally, we reported on the abundance (0.035 ± 0.015 n/m 3 ), morphological characteristics, composition, and sources of atmospheric microplastics in the northwestern South China Sea. Smaller-sized microplastics had a high abundance that decreased with increased proximity from the coast. Most of the detected microplastics were fibers, which accounted for approximately two-thirds of the total quantity. The spectral analysis detected seven polymer types, and polyester was predominant (29%). Combined with the cluster analysis of the backward trajectories of airflow, we demonstrated that the airflow affecting the northwestern South China Sea originated mainly from the northeast, potentially carrying microplastics from cities located in southeastern Chinese provinces to the South China Sea. Highlights: Dry deposition of atmospheric MPs into the northwestern SCS in the fall was 1400 t. The number of MPs gradually increased and peaked as the particle size decreased. The airflow may carry MPs over cities in southeastern China into SCS in the fall. Long-term monitoring of atmospheric MPs and making evaluation standards are needed.